2015
DOI: 10.1176/appi.ajp.2015.14101298
|View full text |Cite
|
Sign up to set email alerts
|

The Brain’s Response to Reward Anticipation and Depression in Adolescence: Dimensionality, Specificity, and Longitudinal Predictions in a Community-Based Sample

Abstract: The findings suggest that reduced striatal activation operates as a mechanism across the risk spectrum for depression. It is associated with anhedonia in healthy adolescents and is a behavioral indicator of positive valence systems, consistent with predictions based on the Research Domain Criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
204
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 260 publications
(224 citation statements)
references
References 37 publications
(33 reference statements)
19
204
1
Order By: Relevance
“…These latter approaches have been mostly consistent in their observation of blunted striatal responses to reward outcomes or reward-predicting cues in MDD patients (Dichter et al, 2009;Forbes et al, 2009;Gotlib et al, 2010;Pizzagalli et al, 2009), and these initial findings have been replicated in recent studies with larger patient samples. Indeed, one recent study of over 1500 adolescents found that reduced ventral striatal activity during reward anticipation was associated with clinical or subclinical depression, and that lower ventral striatal activity in non-depressed teens at the time of scanning was predictive of developing depressive symptoms over a 2-year follow-up period (Stringaris et al, 2015). In addition to neural responses to anticipation, a second recent study identified a failure in the expected temporal shift of striatal responses to reward cues from reward outcomes as a task was learned, a pattern that was specific to patients with greater anhedonia (Greenberg et al, 2015).…”
Section: Reduced Motivation and Psychomotor Function In Psychiatric Dmentioning
confidence: 99%
“…These latter approaches have been mostly consistent in their observation of blunted striatal responses to reward outcomes or reward-predicting cues in MDD patients (Dichter et al, 2009;Forbes et al, 2009;Gotlib et al, 2010;Pizzagalli et al, 2009), and these initial findings have been replicated in recent studies with larger patient samples. Indeed, one recent study of over 1500 adolescents found that reduced ventral striatal activity during reward anticipation was associated with clinical or subclinical depression, and that lower ventral striatal activity in non-depressed teens at the time of scanning was predictive of developing depressive symptoms over a 2-year follow-up period (Stringaris et al, 2015). In addition to neural responses to anticipation, a second recent study identified a failure in the expected temporal shift of striatal responses to reward cues from reward outcomes as a task was learned, a pattern that was specific to patients with greater anhedonia (Greenberg et al, 2015).…”
Section: Reduced Motivation and Psychomotor Function In Psychiatric Dmentioning
confidence: 99%
“…A promising pathophysiological mechanism in depression is that of sensitivity to losses and rewards, with some studies showing either reduced reactivity to rewards (1), or increased reactivity to losses (2, 3), or reduced reactivity to rewards and losses (4). Importantly, studies show that these alterations in reward reactivity are evident in children and adolescents at high risk for developing depression (5, 6) and prospectively predict worsening of depression symptoms (79). However, research on neural correlates of loss or reward sensitivity in adolescent depression is limited in that it has focused almost exclusively on reward sensitivity as well as striatal mechanisms that support it (1, 5).…”
Section: Introductionmentioning
confidence: 99%
“…15,21 However, on a meta-analytic level including studies with unmedicated and medicated patients the association of neural alterations during reward processing and positive symptoms is less clearly delineated. 24 Furthermore, the association between striatal dysfunction and depressive symptoms is well described within depressive disorders 28,29 but data are limited for schizophrenia. 30,31 Most research did not take into account the neural basis of symptom dimensions on a psychosis continuum with broadly defined first-episode psychosis patients or individuals with schizotypal personality traits (SPT).…”
Section: Introductionmentioning
confidence: 99%